Electrical treeing and partial discharge characteristics of silicone rubber filled with nitride and oxide based nanofillers - A. H. M. Nasib; M. H. Ahmad; Z. Nawawi; M. A. B. Sidik; M. I. Jambak (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This article presents a study on electrical treeing performances with its associated partial discharge (PD) and the influence of filler concentration in silicone rubber (SiR) samples which are filled with silicon dioxide (SiO2) and silicon nitride (Si3N4) as nanofillers for electrical tree growth suppression. There are many researches on electrical treeing in SiR with SiO2 nanofillers but none of the publication have reported on Si3N4 nanofillers for suppression of the electrical tree growth. In this study, the treeing experiments were conducted by applying a fixed AC voltage of 10 kV and 12 kV at power frequency of 50 Hz on unfilled SiR, SiR/SiO2, and SiR/Si3N4 nanocomposites with different filler concentrations by 1, 3, and 5 weight percentage (wt%) and the electrical treeing parameters were observed with its correlated PD patterns. The outcome from this study found that the SiR/Si3N4 nanocomposites were able to withstand the electrical treeing better than the pure SiR or SiR/SiO2 nanocomposites. Furthermore, the increase in filler concentration improved the electrical tree performances of the nanocomposites. This finding suggests the Si3N4 can be used as filler in polymeric insulating materials for electrical tree inhibition. Meanwhile, the PD activity shows increment when the tree progresses thereby indicating correlation in both parameters which can be as key parameter for monitoring unseen electrical treeing in the opaque samples.